2018
DOI: 10.1080/2162402x.2018.1471442
|View full text |Cite
|
Sign up to set email alerts
|

Duokines: a novel class of dual-acting co-stimulatory molecules acting in cis or trans

Abstract: Co-stimulatory signals induced by ligands of the tumor necrosis factor superfamily (TNFSF) play a central role in T cell activation and have emerged as a promising strategy in cancer immunotherapy. Here, we established a novel class of bifunctional co-stimulatory fusion proteins with the aim to boost T cell activation at the level of T cell – antigen-presenting cell (APC) interaction. These novel dual-acting cytokine fusion proteins were created by connecting two different homotrimeric TNFSF ligands to form ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Stable transfected HT1080-CD40, HT1080-CD27, HT1080-OX40 and HT1080-4-1BB were kindly provided by Dr. H. Wajant (University Hospital Würzburg, Germany) and were cultivated in RPMI-1640 (Thermo Fisher Scientific, 11875), 10% FBS (Pan Biotech, P30-3309). Mouse melanoma B16-FAP cells 13 were cultured in RPMI-1640, 5% FBS supplemented with 200 μg/mL zeocin (Thermo Fisher Scientific, R25001). Human peripheral blood mononuclear cells (PBMCs) were isolated from buffy coats of healthy donors (Blood bank, Klinikum Stuttgart) by density gradient centrifugation (Lymphocyte Separation Medium 1077, Promocell, C-44010) and cultivated in RPMI-1640, 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stable transfected HT1080-CD40, HT1080-CD27, HT1080-OX40 and HT1080-4-1BB were kindly provided by Dr. H. Wajant (University Hospital Würzburg, Germany) and were cultivated in RPMI-1640 (Thermo Fisher Scientific, 11875), 10% FBS (Pan Biotech, P30-3309). Mouse melanoma B16-FAP cells 13 were cultured in RPMI-1640, 5% FBS supplemented with 200 μg/mL zeocin (Thermo Fisher Scientific, R25001). Human peripheral blood mononuclear cells (PBMCs) were isolated from buffy coats of healthy donors (Blood bank, Klinikum Stuttgart) by density gradient centrifugation (Lymphocyte Separation Medium 1077, Promocell, C-44010) and cultivated in RPMI-1640, 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by combining two different members of the TNFSF into one molecule connecting either single subunits of two ligands (so-called Duokines, Dk) or single-chain derivatives of the ligand (single-chain Duokines, scDk) by flexible linkers. 13 We have demonstrated that these dual-acting costimulatory molecules can activate two different receptor types either on the same cell (i.e. acting in cis) or on different cell types (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-cytokine antibody fusions have been described for IL2 and IL12 [160][161][162], IL12 and GM-CSF [161], TNF and IL2 [57], as well as IL15 and 4-1BBL [40]. The group of Roland Kontermann has introduced the concept of Duokines, dual-acting cytokine fusion proteins generated by connecting two TNF superfamily members (combinations 4-1BBL, OX40L and CD27L) by a flexible peptide linker in different conformations [163].…”
Section: Other Cytokine Payloadsmentioning
confidence: 99%
“…The development of bispecific CD40 agonists is challenging due to the ambiguous expression profile of CD40, nevertheless attempts have been made to target CD40-expressing tumors using CD40/mesothelin-bispecific constructs (ABBV-428, NCT02955251, currently recruiting), CD40/HER2-bispecific constructs 78 and so-called duokines. 79 Additional CD40 bispecifics are on the way, including CEA and others as tumor-targeting antigen. 80…”
Section: Side Effects (Independent Of Agonistic Activity)mentioning
confidence: 99%